2020
DOI: 10.1038/s41598-020-68437-w
|View full text |Cite
|
Sign up to set email alerts
|

Injection of seminal fluid into the hemocoel of honey bee queens (Apis mellifera) can stimulate post-mating changes

Abstract: Honey bee queens undergo dramatic behavioral (e.g., reduced sexual receptivity), physiological (e.g., ovary activation, ovulation, and modulation of pheromone production) and transcriptional changes after they complete mating. To elucidate how queen post-mating changes are influenced by seminal fluid, the non-spermatozoa-containing component of semen, we injected queens with semen or seminal fluid alone. We assessed queen sexual receptivity (as measured by likelihood to take mating flights), ovary activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 157 publications
(248 reference statements)
0
10
0
Order By: Relevance
“…LRTs from MAG extract-injected and mated females had lower transcript levels of AAEL008342, which encodes a monocarboxylate transporter. Monocarboxylate transporters were also down-regulated in female honeybees injected with seminal fluid when compared to buffer-injected [ 105 ]. Down-regulation of oxidoreductase (AAEL09685) and up-regulation of AAEL012382, which contains a predicted C-terminal nucleosidase domain, and of AAEL014719, an inosine-uridine preferring nucleoside hydrolase, were also detected.…”
Section: Resultsmentioning
confidence: 99%
“…LRTs from MAG extract-injected and mated females had lower transcript levels of AAEL008342, which encodes a monocarboxylate transporter. Monocarboxylate transporters were also down-regulated in female honeybees injected with seminal fluid when compared to buffer-injected [ 105 ]. Down-regulation of oxidoreductase (AAEL09685) and up-regulation of AAEL012382, which contains a predicted C-terminal nucleosidase domain, and of AAEL014719, an inosine-uridine preferring nucleoside hydrolase, were also detected.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the processes occurring during male maturation, the development of the reproductive system undoubtedly has the greatest impact on male reproductive success; it generally includes the production of seminal fluids and mucus matter by the seminal vesicles and accessory glands and the migration of spermatozoa from the testes to the seminal vesicles [ 45 , 46 , 47 ]. The seminal fluids contain proteins, sugars, and phospholipids, and the accessory secretions are composed of cyclic peptides and fatty acids that create a viscous texture that will serve as mating plugs; these gland products are transferred to the female during copulation, where they protect the sperm and maintain its viability, but also induce physiological and behavioral changes in the female’s body that increase the chances of successful insemination by the male [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In honeybees, studies have demonstrated that larval nutrition plays a central role in determining male reproductive quality, while protein intake during adulthood has no effect on sperm quality [ 6 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The semen of A. mellifera is so effective at keeping sperm alive that the positive effects can last up to 24 h. The presence of proteins in semen and their structural integrity are critical to this effect, which cannot be replicated by ordinary protein substitutes [116]. Moreover, semen fluids are largely responsible for stimulating postmating changes in queen behavior and physiology, e.g., reduced sexual receptivity, reduced attraction to light, reduced mating flight, ovary activation, ovulation, modulation of pheromone production and transcriptional changes in queens [117,118]. Honeybee drone seminal fluid could induce a decline in queen vision by causing substantial gene expression changes in the brain and perturbing the phototransduction pathway to reduce queen promiscuity across mating flights [18].…”
Section: Gland Proteinsmentioning
confidence: 99%